Dicalcogenetos de metais de transição em poucas camadas: o papel das espécies de calcogênio e suas propriedades não convencionais - Bracht, Jean Michel (Universidade Federal de São Carlos, 2024)
Two-dimensional (2D) Transition Metal Dichalcogenides (TMDs) constitute the most studied class of 2D materials after graphene, as they have a variety of applications already demonstrated in the laboratory, including sensors, nanoelectronics and catalysis. In this context, simulations based on Density Functional Theory (DFT) allow exploring different compositions and crystalline phases, searching for the most promising ones for specific applications. This doctoral thesis presents a systematic investigation of few-layer 2D TMDs with compositions MQ2, where M belongs to the groups 8 and 10 of the periodic table and Q=S, Se or Te. We investigate systems that vary between one and six in the number of layers. Our study focuses on elucidating the structural, energetic and electronic properties of these materials through DFT-based numerical simulations. The structures are optimized with the GGA-PBE semi-local exchange-correlation functional, where we included the D3 van de Waals correction on the forces and total energy. Furthermore, we incorporate corrections for the self-interaction error inherent in PBE through the HSE06 hybrid functional and spin-orbit coupling. Our investigation reveals significant variations in lattice parameters and exfoliation energies with changes in the number of layers, mostly influenced by chalcogen species. Compositions with transition metals within the same column of the periodic table exhibit similar lattice parameters for the same choice of chalcogens, making them suitable for constructing commensurable heterostructures. Furthermore, the decreasing electronegativity trend from S to Te results in stronger exfoliation energies due to lower surface charges, thus governing the structural and electronic characteristics of these materials. We delved deeper into the electronic properties, and found unusual features in other materials, such as (i) increases in band gap generated by spin-orbit coupling for certain compositions, (ii) emergence of polarization electric fields due to the breaking of point inversion symmetry, and (iii) semiconductor-to-metal transitions with the addition of just one or two sheets to the monolayer. The presence of sulfur on the surface results in greater variations in the work function (in relation to the Se and Te terminations) when the number of layers varies, allowing precise adjustment of the work function and electronic affinity with the number of layers and with the choice of transition metal species. These findings highlight the unique and versatile nature of TMDs from groups 8 and 10, motivating diverse applications in nanoelectronics and catalysis, where tuning properties with the number of layers can be leveraged for technological advances.
Few-layer transition metal dichalcogenides: the role of chalcogen species and their unconventional properties
Keywords: Dicalcogenetos de metais de transição; Teoria do funcional da densidade; Poucas camadas; Cálculos de energia total; Propriedades eletrônicas; Função trabalho; Alinhamento de bandas; Transition metal dichalcogenides; Density functional theory; Few-layers; Total energy calculations; Electronic properties; Work function; Band alignment; CIENCIAS EXATAS E DA TERRA::FISICA; CIENCIAS EXATAS E DA TERRA::FISICA::FISICA ATOMICA E MOLECULAR::ESTRUTURA ELETRONICA DE ATOMOS E MOLECULAS; TEORIA